Social support in the formation of street children's identity - Aisha Qori Aina; Johanna Debora Imelda (Journal of Youth and Outdoor Activities, 2025)
Background: Street children face significant challenges in identity formation due to economic pressures, social stigma, and lack of access to self-exploration. This study aims to describe social support in identity formation among eight street children in Penjaringan Village, North Jakarta, using descriptive qualitative methods through interviews and observations. Findings: This study consistently shows that social support helps adolescents and young adults overcome developmental crises and challenges. Therefore, it is important to understand how the type of support they receive on the streets shapes their current identity status. Methods: This study uses a descriptive qualitative approach to describe in depth the sources and forms of social support received in identity formation among street children in Penjaringan Village, North Jakarta. Conclusion: The results show that most street children are in a state of identity moratorium or identity confusion due to difficulties in exploring roles and making commitments. Some informants exhibited characteristics of identity coercion and identity achievement in certain aspects. Social support has been shown to be important in identity formation. Comprehensive and effective support from various sources and forms facilitates more focused role exploration and clearer identity commitments. However, the nature and perception of support are also crucial. Novelty/Originality of this article: Real, personalized support helps adolescents better navigate identity crises, leading to a productive identity moratorium or even identity achievement. Research concludes that social support plays a role in helping street youth navigate the complexities of identity formation.